2016
DOI: 10.1037/hea0000238
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and patterns of fear of cancer recurrence in breast cancer survivors.

Abstract: These study findings support the use of the CBM in predicting which cancer survivors experience greater FCR and indicates that CBM-driven interventions may prove beneficial for reducing distressing FCR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
109
1
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(124 citation statements)
references
References 47 publications
4
109
1
10
Order By: Relevance
“…Handling fear of cancer recurrence or progression is one of the most prominent [9] and common, with moderate to high levels present in 30–70% of cancer survivors [10, 11]. Concerns about additional cancer diagnoses, recurrence, progressions, or death are likely to persist throughout survivorship, as former patients will continue to encounter cancer-related triggers (e.g., follow-up appointments, public health campaigns, new diagnoses in family or friends) after treatment ends [12, 13, 34]. In line with these findings, survivors in the present study on average endorsed moderate to high levels of fear of recurrence or progression.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Handling fear of cancer recurrence or progression is one of the most prominent [9] and common, with moderate to high levels present in 30–70% of cancer survivors [10, 11]. Concerns about additional cancer diagnoses, recurrence, progressions, or death are likely to persist throughout survivorship, as former patients will continue to encounter cancer-related triggers (e.g., follow-up appointments, public health campaigns, new diagnoses in family or friends) after treatment ends [12, 13, 34]. In line with these findings, survivors in the present study on average endorsed moderate to high levels of fear of recurrence or progression.…”
Section: Discussionsupporting
confidence: 88%
“…Chief among these is fear of recurrence or progression [9], with moderate to high levels present in 30–70% of cancer survivors [10, 11]. Fear of recurrence or progression can be triggered by cancer-related stimuli throughout survivorship, such as follow-up appointments [12, 13]. Survivors’ worries about disease recurrence or progression may continue for years after treatment ends [12, 14, 15] and can persist at levels equal to that experienced at the time of diagnosis [16].…”
Section: Introductionmentioning
confidence: 99%
“…In breast cancer survivors who were getting their mammograms, women who reported greater perceived risk, lower coping self-efficacy and greater reassurance-seeking behaviors were more likely to be in the higher FOR group. 50 Unsurprisingly, FOR tends to increase around the time of scans or other testing for recurrence. 51 FOR may be important to address as it has been related with negative health behaviors such as smoking and lower levels of physical activity.…”
Section: Anxiety and Depression In Different Populations Of Survivorsmentioning
confidence: 99%
“…In recently published studies, a variety of factors were found to be associated with the cancer patients’ FCR level. Demographic characteristics such as female gender, young age, living apart or divorce, a higher level of education, and no children have been reported to be related to higher FCR.…”
Section: Introductionmentioning
confidence: 99%